Trends in net survival from pancreatic cancer in six European Latin countries: results from the SUDCAN population-based study. (January 2017) - Bouvier, Anne-Marie; Bossard, Nadine; Colonna, Marc; Garcia-Velasco, Adelaida; Carulla, Maria; Manfredi, Sylvain
Abstract : Pancreatic cancer represents a real clinical challenge. The aim of the SUDCAN collaborative study was to compare the net survival from pancreatic cancer between six European Latin countries (Belgium, France, Italy, Portugal, Spain and Switzerland) and provide trends in net survival and dynamics of excess mortality rates up to 5 years after diagnosis. The data were extracted from the EUROCARE-5 database. First, net survival was studied over the period 2000–2004 using the Pohar-Perme estimator. For trend analyses, the study period was specific to each country. Results were reported from 1992 to 2004 in France, Italy, Spain and Switzerland and from 2000 to 2004 in Belgium and Portugal. These analyses were carried out using a flexible excess rate modelling strategy. There were little differences between countries in age-standardized net survivals (2000–2004). The 5-year net survival was poor (range: 6–10%). The changes in net survival from 1992 to 2004 were mostly related to early survival and patients aged 60 years. A slight decrease in the excess mortality rate between 1992 and 2004 was observed, limited to the 18 months after diagnosis. This study confirmed that, despite some improvement, survival from pancreatic cancer is still poor throughout European Latin countries. The major improvements in clinical imaging did not result in improvements in prognosis. Development of truly innovative treatments is highly needed to improve prognosis. Abstract : Supplemental Digital Content is available in the text.